JAPAN ADULT VIDEO (STUDI KASUS 4 MAHASISWA UNIVERSITAS GADJAH MADA PENGGEMAR JAV) - , MUHAMMAD NAUFAL R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Japan Adult Video, known as JAV, is one of Japanese cultural product which is also included a long history in the process. After internet had been appeared, many peoples could have any information from the other countries without spend up much money and time. Facilities that offered by internet also prevail in JAV which is makes JAV known by Indonesian people who lived in non pornography country such as Indonesia. The emerge of JAV within Indonesian people, definitely became polemic against Indonesian government where everyone pay an attention about the weak governmentâs protection against outsider provocation. Regardless on that thing, now JAV has been one of additional new entertainment among the fans. Based on research from 4 informants, theyâre all think that JAV is more in creativity than earlier adults content that came to Indonesia. Furthermore, JAV represent as a new way in the group interaction between consumers, where, according to John Storey, generally consumers are tend to enjoy in group. But, in the JAV case, the consumers tends to enjoy JAV narcistically, and being in groupâs only for sharing collection as fulfill consumption purpose only.